The Effect of Serif and San Serif Typeface of Luxury Fashion Logotype on Chinese Consumers’ Brand Perception - Zheng, Wang; Kanyan, Louis Ringah; Shanat, Musdi (2022)
An appropriate and well-designed logotype is essential to create brand awareness and positive brand perception. The effect of different typeface has not been well researched in the luxury fashion sector. Extending previous finding regarding typeface application, the two studies tested the effect of Serif and San Serif typeface: the three experiments tested the influence of Sans and Serif on brand perception. The study 1 (N = 102) tested the visual complexity in serif and san serif typeface; the study 2 (N = 134) further investigated the visual simplicity and perceived luxury. The study 3 (N = 92) studied on the brand gender from those two typefaces. The result from those three studies suggested that the serifty peface is structurally more comp…lex than san serif, however, it does not impact on the perceived luxury too much. The san serif typeface is perceived with more masculine than serif, and the gender perception difference is grater among male consumer than female consumers.